Can farmland transfer reduce vulnerability as expected poverty? Evidence from smallholder households in rural China - Chen, Jie; Yang, Mingwei; Zhang, Zhiyong; Wang, Zheng; Zhang, Jianyu (Frontiers in Sustainable Food Systems, 2023)
Extant literature has extensively explored farmland transfer 's impacts, confirming its essential role in poverty alleviation. However, most studies focus on poverty measures that exclusively emphasize current poverty status without adequately addressing the potential of falling into or remaining in poverty. Furthermore, the role of farmland transfer in helping the smallholder households in rural areas appears to be underexamined in the literature. To address this knowledge gap, this study investigates whether farmland transfer can reduce household vulnerability to poverty. A theoretical framework is developed to capture the mechanism by which farmland transfer has a vital role in smallholder households and impacts the probability of being poor in the future. The China Family Panel Studies Survey data set from 2010 to 2018 is used to explore this issue. The results show that land transfer-out households are seemingly the most effective at reducing vulnerability, whereas the reduction effect is not obvious among transfer-in households. Specifically, the vulnerability of transfer-out households is reduced by about 39.52%. Furthermore, we analyze the reasons for heterogeneity in the poverty reduction effects and find that the key mechanism is on the labor resource allocation decision. Actually, for transfer⁃out households, farmland transfer can increase the probability of migrant work and business opportunities, as well as the labor input for non⁃agricultural production, which helps to reduce vulnerability to poverty. On the other hand, for transfer⁃in households, they will invest more labor in agricultural production and increase agricultural inputs, whereas increased inputs to agricultural production do not actually reduce vulnerability to poverty. This study provides a new research perspective on the long-term effects of farmland transfer on rural poverty.